Load monitoring on Pilates training: A study protocol for a randomized clinical trial - De Souza Cavina, Allysiê Priscilla [UNESP]; Pizzo Junior, Eduardo [UNESP]; MacHado, Aryane Flauzino [UNESP]; Biral, Taíse Mendes [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Franciele Marques [UNESP] (Springer Nature, 2019)
Background: Currently there are campaigns to raise the awareness of the need to practice physical exercise with several objectives, mainly as a preventive measure. The Pilates method is a form of therapeutic exercise for maintaining and improving health. However, despite being popular, there is still no scientific evidence on the standardization and progression of the method. Therefore, the purpose of this study was to develop a protocol to monitor the progression of daily Pilates loads between the basic, intermediate, and advanced levels, as well as to analyze the effects of the method on psychometric, cardiorespiratory, and autonomic measures. Methods/design: In total, 54 healthy men underwent 36 sessions of Pilates mat work. Before each training session, cardiorespiratory measures, pain (visual analogue scale), and a psychometric questionnaire were collected. Heart rate (HR), subjective perception of effort (SPE), and RR intervals were measured during the sessions and used later in the analysis of the progression of training load by monitoring the internal training load and heart rate variability. At the end of the sessions, cardiorespiratory measures, the visual analogue scale, and the psychometric questionnaire were measured again. After 15 min of rest, the final HR measurement was made and the participants noted the effort on the SPE scale. The psychometric, cardiorespiratory, and autonomic measures were evaluated before and after each of the 36 training sessions. Discussion: This is a parallel randomized clinical trial of standardized Pilates training, with the aim of estimating training loads and measuring the efficacy of Pilates through clinical, cardiorespiratory, and autonomic outcomes. The protocol can easily be reproduced and could be used to support professionals in prescribing the method. Trial registration: ClinicalTrials.gov, NCT03232866. Registered on 28 July 2017.
Keywords: Autonomic nervous system; Exercise; Exercise movement techniques; Heart rate; Monitoring; Physiologic